Market reaction to the FTSE/JSE responsible investment index series - Usher, Hayden Philip (My University, 2019)
Responsible investment has seen considerable growth since the turn of the millennium, and this has spurred the creation and continuous development of responsible investment indexes across the globe. The purpose of this paper is to investigate whether the release of the RI index series contains price sensitive information content and therefore has value relevance for the market. Using event study methodology applied to the six releases of the FTSE/JSE Responsible Investment Index series from October 2015 to June 2018, this paper investigates the impact on the share prices of constituent, included and excluded firms from this index series. The study finds that the release of the constituents of the RI index does not contain new information content while constituents of the RI top 30 experience positive and statistically significant abnormal returns as a result of their constituency. The inclusion of firms on the RI index is not a release of new price-sensitive information, while firms included on the RI top 30 experience a sustained increase in share price throughout the event window. Firms excluded from the RI index and RI top 30 experience negative and statistically significant share returns and the market applies a greater discount toward firms excluded from the RI top 30. Finally, there are statistically significant differences between firms that were included and firms that were excluded from the RI index and the RI top 30 post-announcement date, and this is caused by the market applying a value discount toward firms with deteriorating ESG performance and disclosure. From an investors perspective, investors are able to generate significant arbitrage returns by shorting (longing) shares of firms expected to be to be excluded (included) from the RI index series. Consequently, firms should strive to be included or remain on the RI index series in order to signal the market that there has not been a deterioration in their ESG performance and disclosure, which would have a negative impact on their share price.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Commerce (Accounting)
Keywords: UCTD; FTSE; JSE; Investment Index; Investment; RI index series; Johannesburg Stock Exchange; Investments--South Africa; Investment analysis; SDG-8: Decent work and economic growth